An aminosterol breaks the autocatalytic cycle of Aβ 42 aggregation and protects cell membranes from its soluble aggregates - Lucas B. Fallot; Johnathan R. Pinc; Joseph E. Buselmeier; Julia C. Palchak; Supria S. Shroff; Kaitlyn Zang; Dillon J. Rinauro; Kate M. Bacon; Michael Nguyen; Mary Claire Schleck; Alyssa R. Cornell; Alexandra Oshidar; et al. (Proceedings of the National Academy of Sciences, 2025)
Aberrant aggregates of the 42-residue form of the amyloid-β peptide (Aβ 42 ) are cytotoxic in Alzheimer’s disease (AD). Cost-effective and chronically safe disease-modifying therapeutics are needed to address the AD medical emergency worldwide. To increase our understanding of the mechanisms of Aβ 42 -induced cytotoxicity and to investigate clinically relevant aminosterols, we study the impact of claramine on the aggregation kinetics and properties of Aβ 42 aggregates, as well as the ability of these proteotoxic species to bind and disrupt cell membranes. Whereas previously studied aminosterols accelerated Aβ 42 aggregation, we show that claramine potently inhibits Aβ 42 amyloid fibril formation. We find that claramine stabilizes soluble Aβ 42 , speeding up primary and secondary nucleation into species with antiparallel β-sheet structure that are elongation incompetent, thereby depleting Aβ 42 monomers from the aggregation reaction. This steroid–polyamine also dissociates Aβ 42 fibrillar aggregates, resulting in the abrogation of the autocatalytic capacity of Aβ 42 fibrils, and it also inhibits the aggregation of a tau fragment relevant to AD. Upon exposure of human neuroblastoma cells to stabilized Aβ 42 oligomers, claramine effectively neutralized Aβ 42 oligomer-induced cytotoxicity by preventing their binding to cell membranes. Owing to the unique mechanism of action of aminosterols to reduce the toxicity of soluble Aβ 42 aggregates by protecting cell membranes, and the newly characterized ability of claramine to inhibit Aβ 42 fibril formation and dissociate fibrillar Aβ 42 resulting in the interruption of the positive feedback loop in Aβ 42 aggregation, our findings further emphasize the relevance of this family of natural products as potential treatments for AD and other protein misfolding diseases.